2006
DOI: 10.1203/01.pdr.0000227478.29271.52
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Enhances Lung Maturity in the Fetal Rat

Abstract: Pulmonary alveolar type II cells synthesize and secrete phospholipids and surfactant proteins. In most mammalian species, the synthesis of phospholipids and proteins of lung surfactant increases with fetal lung maturation, which occurs late in gestation. Factors that may promote lung maturation and surfactant production include the placental hormone, leptin, whose expression increases with advancing gestational age. We demonstrate that physiologic concentrations of leptin (1 and 10 ng/mL) increase the levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 32 publications
(32 reference statements)
1
65
1
1
Order By: Relevance
“…Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29). Furthermore, polymorphisms in leptin and leptin receptor have been associated with differences in lung function (30,31).…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have also shown that leptin and leptin receptor are expressed in airway epithelium (24), and bronchial expression of leptin is increased in chronic obstructive pulmonary disease (25,26). Leptin seems to be involved in embryonic lung growth and maturation (27,28), and in fibroproliferative responses in the lung to bleomycin (29). Furthermore, polymorphisms in leptin and leptin receptor have been associated with differences in lung function (30,31).…”
Section: Discussionmentioning
confidence: 97%
“…This result contrasts with several studies carried out during fetal life, demonstrating an important role for leptin in the lung development of different species, such as rodents or primates. 29,30 At that stage, leptin receptors have been identified in the pneumocyte type II cells, which are responsible for synthesizing pulmonary surfactant and are developmentally regulated during late phases of gestation. 29,30 The lack of efficacy of leptin blockage during our study may suggest that its action on lung maturity is probably restricted to the gestational period in normal animals.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…29,30 At that stage, leptin receptors have been identified in the pneumocyte type II cells, which are responsible for synthesizing pulmonary surfactant and are developmentally regulated during late phases of gestation. 29,30 The lack of efficacy of leptin blockage during our study may suggest that its action on lung maturity is probably restricted to the gestational period in normal animals. However, in IUGR animals, postnatal leptin treatment may be effective in correcting developmental defects in the lungs as suggested by our previous study performed in IUGR piglets.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…We detected SP-B (45 kD) and C (21 kD) protein from lung lysates using Western analysis undertaken with antibodies that reacted selectively with SP-B and SP-C (Abcam Inc., Cambridge, MA) and with b-tubulin (Santa Cruz Biotechnology, Santa Cruz, CA) as control, as previously described (20,21).…”
Section: Western Blottingmentioning
confidence: 99%